Sistem Pemantau dan Kendali Tekanan Gas SF6 PMT Gardu Induk Melalui IoT - Rayana Jaka Surya; Gigih Priyandoko; Istiadi Istiadi (Website, 2022)
The design of the monitoring system and automatic control of sulfur hexafluoride gas pressure on the power breaker, is carried out using several components. NodeMCU ESP8266 microcontroller with MPX5700AP air pressure sensor and internet of things device. This system is made to maintain gas pressure on the leaking power breaker due to certain factors. The MPX5700AP air pressure sensor measures the gas pressure on the leaking power breaker with a value parameter of 0 - 2 bar. The test result of voltage output at a pressure of 0 bar is 0.8 volt DC, and for 1 bar is 1.4 volt DC. The analog voltage output is then converted into a digital value in binary form on a microcontroller. NodeMCU microcontroller is a control device equipped with a Wi-Fi module that allows users to control the system wirelessly. Digital data on microcontrollers is then sent to internet of things devices such as blynk software on mobile phones. The command on the microcontroller activates the mosfet module on or off which will open or close the gate on the gas valve solenoid according to the specified digital value data. From the results of 6 tests, there was a ratio of the difference between the output setting in the gas cylinder and the result of filling the gas pressure on the power breaker by 5.43%. Perancangan sistem pemantau dan kendali otomatis tekanan gas sulfur heksafluorida pada pemutus tenaga, dilakukan menggunakan beberapa komponen. Mikrokontroler NodeMCU ESP8266 dengan sensor tekanan udara MPX5700AP dan perangkat internet of things. Sistem ini dibuat untuk menjaga tekanan gas pada pemutus tenaga yang bocor dikarenakan faktor tertentu. Sensor tekanan udara MPX5700AP berfungsi mengukur tekanan gas pada pemutus tenaga yang bocor dengan parameter nilai 0 - 2 bar. Hasil pengujian keluaran tegangan pada tekanan 0 bar adalah 0,8 volt DC, dan untuk 1 bar adalah 1,4 volt DC. Keluaran tegangan analog kemudian diubah menjadi nilai digital dalam bentuk biner pada mikrokontroler. Mikrokontroler NodeMCU merupakan perangkat kontrol yang dilengkapi dengan modul Wi-Fi yang memungkinkan pengguna dapat mengendalikan sistem secara nirkabel. Data digital pada mikrokontroler kemudian dikirim ke perangkat internet of things seperti software blynk pada handphone. Perintah pada mikrokontroler akan mengaktifkan modul mosfet on atau off yang akan membuka atau menutup gerbang pada solenoid valve gas sesuai data nilai digital yang telah ditentukan. Dari hasil 6 kali pengujian, diperoleh perbandingan selisih antara setting output pada tabung gas dengan hasil pengisian tekanan gas pada pemutus tenaga sebesar 5,43 %.